How to get what you want when you do not know what you want: A model of incentives, organizational structure and learning - Luigi Marengo; Corrado Pasquali (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
In this paper we present a model of the interplay between learning, incentives and the allocation of decision rights in the context of a generalized agency problem. Within this context, not only actors face conflicting interests but diverging cognitive isionsof the right course of action as well. We show that a principal may obtain the implementation of desired organizational policies by means of appropriate incentives or by means of appropriate design of the allocation of decisions, when the latter is cheaper but more complex. We also show that when the principal is uncertain about which course of action is more appropriate and wants to learn it from the environment, organizational structure and incentives interact in non-trivial ways and must be carefully tuned. When learning is not at stake, incentives and organizational structure are substitutes. When instead learning is at stake, organizational structure and incentives may complement each other and have to be fine tuned according to the complexity of the learning process and the competitive pressure which is put on fast or slow learning.
Keywords: 330; Incentives; Organizational Structure; Learning